Kajian Visual Terhadap Poster Rewind Art Periode 2010 - 2022 - fitriani, amelia; Oetopo, Astawarin (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
This study aims to analyze posters through visual communication design and the use of posters as a medium to convey information and messages. Visual arts, with inherent beauty that can be perceived through the senses, hold significant meaning in this field. Visual communication design explores creative expression and communication concepts, conveying ideas visually through graphic elements. Posters, as two-dimensional artworks, are analyzed for their effectiveness in publication, communication, and information dissemination. They serve as a means to communicate with the public, facilitating easy information delivery and acting as decorative and promotional elements The research method used is qualitative with a semiotic approach by Charles S. Pierce. The data collection technique employed is interviews with the poster designer of